(-1 3/5 x3 y2) (-1/2 c2 x2)

Amalik0 Amalik0    2   22.11.2021 09:28    0

Ответы
28ByaKa28 28ByaKa28  22.12.2021 09:36

Объяснение:

.......,


(-1 3/5 x3 y2) (-1/2 c2 x2)
ПОКАЗАТЬ ОТВЕТЫ
vbvb2006 vbvb2006  22.12.2021 09:36

Объяснение:

( - 1 \frac{3}{5} x {}^{3} y {}^{2} )( - \frac{1}{2} c {}^{2} x {}^{2} ) =\left(-\frac{1\times 5+3}{5}\right)x^{5}y^{2}\left(-\frac{1}{2}\right)c^{2} =\left(-\frac{5+3}{5}\right)x^{5}y^{2}\left(-\frac{1}{2}\right)c^{2} =-\frac{8}{5}x^{5}y^{2}\left(-\frac{1}{2}\right)c^{2} =\frac{4}{5}x^{5}y^{2}c^{2}

ПОКАЗАТЬ ОТВЕТЫ